Queer utopias and queer criminology - Copson, Lynne (Criminology & criminal justice, 2020)
Drawing on the concept of utopia to reflect upon the emerging field of queer criminology and José Esteban Muñoz’s account of queer theory as essentially utopian, we draw two conclusions. First, we suggest that queer criminology is currently limited by tinkering at the edges with piecemeal reforms instead of focussing on radical, wholesale changes, and second, that queer theory contains within it the potential for a more holistic reimagining of the social world. In doing so, we question rigid cis/trans binaries and reject accounts of trans/gender that ignore the role of structural harm. We draw on Ernst Bloch’s concepts of ‘abstract’ and ‘concrete’ utopia to suggest that while queer criminology has succeeded in producing largely ‘abstract’ utopias, it struggles in translating these into ‘concrete’ ones. By introducing examples of trans literary utopias as potential transformative cultural forms, however, we consider the potential of queer theory for realising ‘concrete’ utopia through a more radical rethinking of the social world.